Natural human apoA-I mutations L141RPisa and L159RFIN alter HDL structure and functionality and promote atherosclerosis development in mice. Issue 1 (November 2015) - Tiniakou, Ioanna; Kanaki, Zoi; Georgopoulos, Spiros; Chroni, Angeliki; Van Eck, Miranda; Fotakis, Panagiotis; Zannis, Vassilis I.; Kardassis, Dimitris
Abstract: Objective: Mutations in human apolipoprotein A-I (apoA-I) are associated with low high-density lipoprotein (HDL) cholesterol levels and pathological conditions such as premature atherosclerosis and amyloidosis. In this study we functionally characterized two natural human apoA-I mutations, L141RPisa and L159RFIN, in vivo . Methods: We generated transgenic mice expressing either wild-type (WT) or the two mutant forms of human apoA-I on a mouse apoA-I −/− background and analyzed for abnormalities in their lipid and lipoprotein profiles. HDL structure and functionality, as well as atherosclerosis development following a 14-week high-fat diet were assessed in these mice. Results: The expression of either apoA-I mutant was associated with markedly reduced serum apoA-I (<10% of WT apoA-I), total and HDL-cholesterol levels (∼20% and ∼7% of WT apoA-I, respectively) and the formation of few small size HDL particles with preβ2 and α3, α4 electrophoretic mobility. HDL particles containing either of the two apoA-I mutants exhibited attenuated anti-oxidative properties as indicated by their inability to prevent low-density lipoprotein oxidation, and by decreased activities of paraoxonase-1 and platelet-activating factor acetylhydrolase. However, the apoA-I(L141R)Pisa or apoA-I(L159R)FIN -containing HDL particles demonstrated increased capacity to promote ATP-Binding Cassette Transporter A1-mediated cholesterol efflux from macrophages. Expression of apoA-I(L141R)Pisa or apoA-I(L159R)FIN mutations in mice was associated with increased diet-induced atherosclerosis compared to either WT apoA-I transgenic or apoA-I −/− mice. Conclusions: These findings suggest that natural apoA-I mutations L141RPisa and L159RFIN affect the biogenesis and the functionality of HDL in vivo and predispose to diet-induced atherosclerosis in the absence of any other genetic defect. Highlights: Transgenic mice expressing human apoA-I(L141R) or (L159R) have very low HDL levels. HDL particles formed in these mice have preβ2 and α3, α4 electrophoretic mobility. Anti-oxidant capacity of HDL containing apoA-I(L141R) or (L159R) is compromised. Both apoA-I mutants are sufficient to promote diet-induced atherosclerosis in mice.